Analisis Kinerja Keuangan Provinsi Jambi - Sudirman Sudirman; Susilawati Susilawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
The contribution of local revenue (PAD) to regional income during the 2012-2016 period on average was 37.99% per annum and for 2012 the contribution of local revenue to regional income was 37.02%. This is due to the fact that the receipt of original regional income from third party contributions is very large. On average during the period of 2012-2016 the ability of local tax is relatively low if linked to the Gross Regional Domestic Product. While the power of regional retribution if associated with Gross Regional Domestic Product is also still relatively low, but has increased from year to year. This shows that management management in receiving regional retribution has increased. On average during the 2012-2016 period the realization of local tax revenues reached 103.63% per year (very effective) from the target of local tax revenue. In addition, the realization of regional retribution revenue reaches 103.20% per year (very effective) from the target of receiving regional retribution. Whereas the realization of BUMD profit income only reached 131.01% per year (very effective) from the target of BUMD profit income and the realization of other revenue from legitimate PAD only reached 109.36% per annum (very effective). On average, the economic growth rate of Jambi Province is 5.18% per year, it is expected that the increase in local tax revenue elasticity will increase by 8.90% per year. elasticity of the increase in regional retribution receipts is 12.91% per year. The dependency ratio of Jambi Province in the period of 2012-2016 was an average of 31.69 percent per year. Jambi province's regional autonomy ratio in the 2012-2016 period is an average of 12 percent per year with instructive conditions means it is very dependent on the central government